Tarsal navicular stress fractures: a rare soccer injury twelve-year follow-up of the first reported case in a professional player and literature review - Barroso Rosa, S.; Aniel-Quiroga Bilbao, M.; De Santos Tena, D. (International Journal of Athletic Therapy & Training, 2023)
Tarsal navicular stress fractures are rare injuries, mostly occurring in long-distance runners, jumpers, and occasionally affecting athletes in high-contact sports such as rugby or American/Australian football. This condition generally represents a clinical challenge, resulting in considerable diagnostic delays. While the ideal treatment is still controversial, surgical treatment seems to provide good results in recovering function and return to play. Tarsal navicular stress fractures have been extremely rare in soccer players; only seven published cases have been located to date. This article is a paradigmatic report on a professional player with this injury and a successful outcome after a 12-year follow-up.